Comparison of variability in diameter and taper of gutta percha cones of diﬀerent brands using Stereomicroscopy and Digital Micrometer - N. Mishra; K. Magwa; M. Agarwal; M. P. Singh; S. Singh; S. Thakur (LLC "Endo Press", 2021)
Aim: Variations in cone tip diameter while obturation can lead to premature binding, extrusion, or poor adaptability of GP to the canal walls and promotes microleakage and ultimately endodontic failure. The purpose of this investigation was to measure the variability from the listed cone tip diameter and taper of size #25, 0.06 taper GP cones from three different brands with the help of stereomicroscope and digital micrometer.Materials and methods: 45 GP points (N = 45) of Size #25 with an 0.06 taper from three different brands were divided into three groups: Group A - Diadent Group B - K3 and Group C Pro- Taper Next. Each group have 15 GP (n = 15). The diameters (D0 and D3), tapers were measured according to the ANSI/ADA Specification No. 78 using stereomicroscope (accuracy of 0.001mm) and digital micrometer. Kruskall Wallis test was to detect any significant differences between two or more groups and Mann Whitney U test for pairwise comparison. p value < 0.05 were considered as statistically significant.Results: On comparing there was significant variability within the three brands using stereomicroscopy, the standard values for D0 diameter which was 0.25 ± 0.23, Protaper Next GP cones was the similar to the standardized values compared to Diadent and K3 GP cones which were significantly different from the standard values. On comparing diameter variation at D3, Protaper Next, 0.043 ± 0.018 was once again similar to its manufacturer standard values of 0.43 ± 0.022. Diadent showed mild variation with D3 Diameter of 0.44 ± 0.017 and K3 was significantly different from the standard values K3 was 0.41 ± 0.018.Conclusions: The results of the current study indicate significant variability between GP cone brands for both diameter and taper. However, the high standard deviation values associated with most of the diameter and taper differences from manufacturer's nominal values also suggests high variability within individual brands.